Not a Babe, Certainly not a Mouth: On a Supposed Word for “Child” – not Found at Hibis Temple - Klotz, David (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
Response to “Out of the Mouths of Babes” by Benjamin Hinson (ZÄS 144/1). The alleged word for “child” is based on an erroneous reading. Parallels show this is a very different epithet (“he who ejaculates the Nun waters”), most likely denoting Atum.